Perioceutics: Matrix metalloproteinase inhibitors as an adjunctive therapy for inflammatory periodontal disease - Esther Nalini Honibald; Sebeena Mathew; Jeyantha Padmanaban; Elanchezhiyan Sundaram; Renuka Devi Ramamoorthy (Wolters Kluwer Medknow Publications, 2012)
Matrix metalloproteinases (MMPs) form a group of more than 20 zinc-dependent enzymes that are crucial in the degradation of the main components in the extracellular matrix, and thereby play important roles in cell migration, wound healing, and tissue remodeling. MMPs have outgrown the field of extracellular matrix biology and have progressed toward being important regulatory molecules in inflammation, and hence are key components in the pathogenesis of periodontitis. This rise in status has led to the development of MMP inhibitors which can act as switches or delicate tuners in acute and chronic inflammation and the regenerative phase after inflammation. The new challenge in MMP research is to better understand the complex role these enzymes play in periodontal disease and to design inhibitors that are successful in the clinic. Perioceutics or the use of the pharmacological agents specifically developed to manage periodontitis is an interesting and emerging aid in the management of periodontal diseases along with mechanical debridement. The purpose of this review is to provide an introduction to MMPs and their inhibitors, the pathologic effects of a disturbance in the functions of enzyme cascades in balance with natural inhibitors, and highlight on the adjunctive use of MMP inhibitors in periodontal therapy and some of the current challenges with an overview of what has been achieved till date.